Information and Willingness to Pay in a Contingent Valuation Study: The Value of S. Erasmo in the Lagoon of Venice - Anna Alberini; Paolo Rosato; Alberto Longo; Valentina Zanatta (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper reports on a contingent valuation study eliciting willingness to pay for a public program for the preservation of lagoon, beach and infrastructure in the island of S. Erasmo in the Lagoon of Venice. A referendum dichotomous choice approach with a follow-up question is used to obtain information about willingness to pay from a sample of residents of the Veneto Region in Italy. We use split samples to investigate the effect of providing different levels of information to respondents before asking the payment questions. Our experimental treatment is a reminder of possible reasons for voting in favor or against the proposed program before the referendum question. We find that reminding respondents of the reasons for voting for or against the public works increases WTP among less highly educated respondents, and decreases WTP among more highly educated respondents.
Keywords: Q0; Q3; Q26; 330; Contingent valuation; Effects of information; Gewässerschutz; Zahlungsbereitschaftsanalyse; Informationsversorgung; Venedig